A feedforward circuit between KLF5 and lncRNA KPRT4 contributes to basal-like breast cancer. (28th May 2022) - Du, Guangshi; Sun, Jian; Li, Zhen; Zhang, Qian; Liu, Wenjing; Yang, Chuanyu; Zhao, Ping; Wang, Xinye; Yin, Qiyan; Luo, Yao; Song, Jinhuan; Wen, Yi; et al.
Abstract: Basal-like breast cancer (BLBC) is the most aggressive subtype of breast cancer with a poor prognosis. Long noncoding RNAs (lncRNAs) play critical roles in human cancers. Krüppel-like Factor 5 (KLF5) is a key oncogenic transcription factor in BLBC. However, the underlying mechanism of mutual regulation between KLF5 and lncRNA remains largely unknown. Here, we demonstrate that lncRNA KPRT4 promotes BLBC cell proliferation in vitro and in vivo . Mechanistically, KLF5 directly binds to the promoter of KPRT4 to promote KPRT4 transcription. Reciprocally, KPRT4 recruits the YB-1 transcription factor to the KLF5 promoter by interacting with YB-1 at its 5′ domain and forming an RNA-DNA-DNA triplex structure at its 3′ domain, resulting in enhanced transcription of KLF5 and ultimately establishing a feedforward circuit to promote cell proliferation. Moreover, the antisense oligonucleotide (ASO)-based therapy targeting KPRT4 substantially attenuated tumor growth in vivo . Clinically, the expression levels of YB-1, KLF5 and KPRT4 are positively correlated in clinical breast specimens. Together, our data suggest that KPRT4 is a major molecule for BLBC progression and that the feedforward circuit between KLF5 and KPRT4 may represent a potential therapeutic target in BLBC. Highlights: KPRT4 is a new oncogenic lncRNA and specific target of KLF5 in BLBC. KPRT4 in turn enhances the transcription of KLF5 by recruiting YB-1 to KLF5 promoter through forming an RNA-DNA-DNA triplex, establishing a feedforward circuit to promote cell proliferation in BLBC. The KPRT4-ASO-based therapy significantly suppressed tumor growth in vivo, implying that KPRT4 is a promising therapeutic target for BLBC.